Immediate breast reconstruction with a ‘modified fleur-de-lis’ abdominal-free flap in a patient with previous abdominal surgery - Manuel Robustillo; Luis Parra Pont; Georgios Pafitanis; Pedro Ciudad; Daniel Grandes; Israel Iglesias (Indian Journal of Plastic Surgery)
DIEP flap has become the gold standard method for patients undergoing autologous breast reconstruction; however, previous surgery or scars in the abdominal area have been considered a relative contraindication for the use of abdominal tissue. Longitudinal midline abdominal scars may be specially problematic because of the poor midline crossover of blood and the high risk of necrosis of the distal flap. Patients with small breast may be easily reconstructed with hemi-DIEP flap; however, patients with large breast need more tissue available. Our aim is to report a modification of a ‘fleur-de-lis pattern’ for a breast reconstruction in a patient with previous abdominal surgery and large breast. The post-operative course was uneventful, flap did not show blood supply compromise, volume and symmetry are preserved after 6 months post-operative and donor site morbidity has not been observed. This modification may be very useful to avoid complications related to poor blood supply associated with scar tissues. Careful pre-operative planning and the transfer of only well-vascularised tissue are essential for a successful reconstruction.